Centrifugal propagation of motion adaptation effects across visual space - McGraw, Paul V.; Roach, Neil W. (Association for Research in Vision and Ophthalmology (ARVO), 2008)
Perceptual distortions induced by adaptation (aftereffects) arise through selective changes in the response properties of discrete subpopulations of neurons tuned to particular image features at the adapted spatial location. The systematic and well-documented increase of cortical receptive field sizes with eccentricity dictates that visual aftereffects ought to become less tightly tuned for location as stimuli are moved away from fixation. Here, we demonstrate that while this pattern holds for archetypal orientation and spatial frequency aftereffects, the effects of motion adaptation are characterized by precisely the opposite relationship. Surprisingly, adaptation to translational motion close to fixation induces distortions of perceived position and dynamic motion aftereffects that propagate centrifugally across visual space, resulting in a lack of location specificity. In contrast, motion adaptation in more peripheral locations produces aftereffects that are largely limited to the adapted spatial region. These findings suggest that central motion adaptation has the unique capacity to influence the response state of spatially distant neural populations that do not themselves encode the adapting stimulus.